PEMANFAATAN SERBUK KAYU JATI (Tectona grandis L.) YANG DIRENDAM DALAM AIR DINGIN SEBAGAI MEDIA TUMBUH JAMUR TIRAM (Pleurotus comunicipae) - . Baharuddin; Muh. Taufik Arfah; . Syahidah (Forestry Faculty of Universitas Hasanuddin, 2006)
The growth responds of Pleurotus comunicipae to the use of cold water-soaked teakwood sawdust as a growth medium was investigated. Teakwood sawdust was soaked in cold water during the time periods of 1, 3, 5 and 7 days) with ten replications. Unsoaked teakwood sawdust was also prepared and used as a control. Measurement variabels consisted of time required for a completely covering mycelial growth, number of fruitbody, and fungal mass (green and dry weight). Results showed that P. comunicipae placed on soaked teakwood sawdust medium had a better growth than control (without soaking) medium. The medium with increased soaking period produced a good growth ability of P.comunicipae. At teakwood sawdust soaked for 7 days, the average of mycelial growth to cover teakwood sawdust medium, number of fruiting bodies, green weight and dry weight at the first harvesting were 52.6 days, 8.6 units, 100.5 grams and 13.4 grams, respectively. Keywords: teakwoods sawdust, Pleurotus comunicipae, cold water soaking, growth ability